Does the East Get What Would Otherwise Flow to the South? FDI Diversion in Europe - Daniel Piazolo; Robert M. Kokta; Claudia M. Buch (Kiel Institute of World Economics (IfW), 2001)
This paper examines the FDI flows towards two regions in the periphery of Europe: the Central and Eastern European countries (CEECs) and the countries of Southern Europe. We investigate whether evidence exists for FDI diversion from Southern Europe to the CEECs. A cursory observation of recent FDI trends might give rise to such claims of diversion. On the basis of gravity model equations, this paper compares the expected and actual FDI figures. The findings lead us to conclude that there is no evidence of FDI diversion between these two regions.
Keywords: F15; F21; 330; European Integration; Transition Economies; FDI; Gravity Model.; Direktinvestition; Räumliche Verteilung; Gravitationsmodell; Wirtschaftsintegration; Schätzung; Osteuropa; Südeuropa; Europa